An in situ extraction and derivatization method for rapid analysis of short-chain fatty acids in rat fecal samples by gas chromatography tandem mass spectrometry. Issue 15 (31st March 2017) - Park, Na Hyun; Kim, Min-Sun; Lee, Wonwoong; Lee, Myoung Eun; Hong, Jongki
Abstract : Rapid determination of SCFAs in rat fecal samples by GC-MS/MS combined with in situ extraction and derivatization. Abstract : Short-chain fatty acids (SCFAs) are major products of gut microbial fermentation and changes in their levels in a biological system reflect the progress of various diseases. However, analysis of SCFAs in biological samples is limited due to their easy loss during sample workup, their low concentrations, and the coexistence of matrices. In this study, we developed a feasible method for the analysis of SCFAs in rat fecal samples using gas chromatography-tandem mass spectrometry (GC-MS/MS) combined with an in situ extraction and derivatization method. More specifically, in situ extraction and derivatization were applied for the determination of SCFAs using tetrabutylammonium hydrogen sulfate (TBAHS) and pentafluorobenzyl bromide (PFBBr). TBAHS concentration and pH values, as well as the temperature and time of the derivatization reaction were effectively optimized. Moreover, the proposed process reduced the analysis time and limited the loss of SCFAs during the sample workup. It also improved their peak shapes and resulted in longer GC retentions and high sensitivity in MS detection. Use of GC-MS/MS could offer high sensitivity and selectivity for SCFA-PFB derivatives in complicated matrix samples by selecting a multiple-ion reaction monitoring (MRM) transition ion at m / z 181 that corresponds to the [PFB] + ion. The established method was also validated in terms of linearity, limits of detection (LODs) and quantification (LOQs), and matrix effects. It was proved to be linear ( r 2 > 0.997), with lower LODs of 5–24 ng mL −1, and lower LOQs of 0.05–0.1 μg mL −1 for all SCFAs. The proposed method will be useful for the determination of SCFAs in rat fecal samples and for the clinical diagnosis of various diseases.